Optimisation of a suppression and replacement therapeutic strategy for animal models of rhodopsin-linked autosomal dominant Retinitis Pigmentosa - Kilty, Claire (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2012)
The focus of research presented in this PhD thesis was optimising a therapeutic strategy for an inherited retinal disorder termed Retinitis Pigmentosa (RP). RP is a disease in which the photoreceptors progressively degenerate. This initiates with degeneration of rod cells and as the disease progresses typically the cone photoreceptors are also affected. At the end stage of the disease affected individuals are legally blind. RP can be inherited as an autosomal dominant (adRP), autosomal recessive or x-linked recessive condition, although digenic and mitochondrial inherited forms of the disease have also been characterised.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.